Inspiratory muscle training and endurance: A central metabolic control perspective - Edwards, A. M.; Walker, R. E. (International Journal of Sports Physiology and Performance, 2009)
The efficacy of inspiratory muscle training (IMT) has been the subject of considerable controversy in terms of whether it is beneficial to endurance athletes and because a convincing physiological rationale has not been identified to explain its mechanism of action. Early studies suggested that IMT was an ineffectual intervention for gains in either maximal aerobic power or endurance-specific performance. More rigorous recent research supports the observation that maximal aerobic power is not receptive to IMT; however, closer evaluation of both early and contemporary research indicates that responses to endurance-specific performance tests are sensitive to IMT. As the aim of endurance training is to improve endurance performance rather than maximal aerobic power, it is plausible that IMT may be useful in specific performance-related circumstances. Performance adaptations following IMT appear to be connected with posttraining reports of attenuated effort sensations, but this common observation has tended to be overlooked by researchers in preference for a reductionist explanation. This commentary examines the pertinent research and practical performance implications of IMT from the holistic perspective of complex central metabolic control.